Full-colour double-virtual amplitudes for associated production of a Higgs boson with a bottom-quark pair at the LHC - Simon Badger; Heribertus Bayu Hartanto; Rene Poncelet; Zihao Wu; Yang Zhang; Simone Zoia (Journal of High Energy Physics)
Abstract We present the double-virtual amplitudes contributing to the production of a Higgs boson in association with a b b ¯ $$ b\overline{b} $$ pair at the Large Hadron Collider. We perform the computation within the five-flavour scheme, which employs massless bottom quarks and finite bottom-Yukawa coupling, taking into account all the colour structures. We derive the analytic form of the helicity amplitudes through finite-field reconstruction techniques. The analytic expressions have been implemented in a public C++ library, and we demonstrate that evaluations are sufficiently stable and efficient for use in phenomenological studies.